DESAIN MANAJEMEN KURIKULUM PENDIDIKAN KARAKTER ISLAM DALAM MEMBENTUK INSAN KAMIL (STUDI KASUS DI SMP AL-IRSYAD AL-ISLAMIYYAH PURWOKERTO) - Nugroho, Sapto Sri; Roqib, Mohammad (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2023)
The decline in morality and quality of the nation's children in this country indicates that there is a mistake in the world of our education, education itself should function as a space and process of humanization for all students and students who are currently pursuing education, both formal and non-formal, education should not only focus on the growth and development of various potentials that exist within students but furthermore it can become a strategic forum and internalization of values, ethics, morals and the main character of students so that they become individuals who, not only excel in terms of science and technology, but also based on high morals and etiquette. The research method used is qualitative with a descriptive approach. The results of the research are that to realize the human attitude of students in the Al-Irsyad Al-Islamiyyah Middle School Purwokerto school environment, it must start from the agreement of all parties, which includes several parties involved, including the school, teachers and students, then to create human beings. Kamil, students and teachers at Al-Irsyad Al-Islamiyyah Middle School, Purwokerto, must practice the values shared together to become a strong commitment to the values of community life and all aspects that bind them, including the formation of character education which has the noble goal of balancing between religious interests and ideal social needs, apart from that there are several messages that serve as a reference for all school members to always prioritize the values of character education in accordance with the teachings of the Islamic religion. Thus, character education which aims to form human beings can be seen from its main benchmark, namely understanding values and norms originating from religious teachings, which are then combined as one of the components of a character-based curriculum, meaning the values that are manifested in human morals. can be agreed upon as a character and can be well accepted by all members of the school community and social environment.